Incidence, in-hospital mortality and risk factors for hospital-acquired pneumonia in patients with intra-abdominal surgical procedures hospitalized in a tertiary hospital in Belgrade, Serbia: A matched case- control study - Taušan Đorđe; Kostić Zoran; Slavković Damjan; Nešković Branimir; Bokonjić Dubravko; Šipetić-Grujičić Sandra; Ratković Nenad; Šuljagić Vesna (Vojnosanitetski Pregled)
Background/Aim. Hospital-acquired pneumonia (HAP) in a surgical population significantly increases morbidity and mortality, prolongs hospitalization and increases total treatment costs. In the present study, we aimed to determine incidence, in-hospital mortality and risk factors (RFs) of HAP in patients with intra-abdominal surgical procedures hospitalized in a tertiary hospital in Belgrade (Serbia). Methods. Through regular hospital surveillance of patients who underwent intra-abdominal surgical procedures, we prospectively identified postoperative HAP during five years. In the matched case-control study, every surgical patient with HAP was compared with four control patients without HAP. In the group of patients with HAP, those who died were compared with those who survived. Results. Overall 1.4% of all intra-abdominal surgical patients developed HAP in the postoperative period. The incidence of HAP (per 1,000 operative procedures) was greatest in patients undergoing exploratory laparotomy (102.6), followed by small bowel surgery (36.6), and gastric surgery (22.7). Multivariate logistic regression analysis (MLRA) identified three independent risk factors (RF) associated with HAP: multiple transfusion [p = 0.011; odds ratio (OR): 4.26; 95% confidence interval (CI): 1.59–11.33], length of hospital stay (p = 0.024; OR: 1.02; 95%CI: 1.00–1.03) and hospitalization in the Intensive care unit (ICU) (p = 0.043; OR: 2.83; 95%CI: 1.03–7.71). MLRA identified only surgical site infection as an independent RF associated with the poor outcome of HAP (p = 0.017; OR: 5.929; CI95%: 1.37–25.67). Conclusion. The results of the present study are valuable in documenting the relations between RFs and HAP in patients undergoing intra- abdominal surgical procedures.